Eksplorasi Pengetahuan Masyarakat Pandalungan Terhadap Tanaman Kelor (Moringa oleifera) Di Kecamatan Prigen Kabupaten Pasuruan - Khamidatul Ula; Ari Hayati; Hasan Zayadi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2020)
Moringa oleifera is the traditional medicinal plant in Indonesia and it has a complete source of nutrition and it is beneficial to human health from its roots, stems, leaves and fruit. The utility of plants in life is a part of Botany that can be studied through the branch of Biology, Ethnobotany. The aims of this study was to determine the benefits, description and distribution of Moringa plants in Jatiarjo and Dayurejo Village in Prigen District, Pasuruan. This study uses descriptive methods which include: literature study, field observations, structural interviews and open manner, data analysis and documentation of the distribution of Moringa oleifera villages. The results of this study indicate the potential of Moringa oleifera plant in Dayurejo Village as a traditional medicine of 28%, a food ingredient of 30%, a hedgerow of 20%, traditional ritual of 10%, and an additional economic value of 12%. Whereas in Jatiarjo Village as food of 40%, traditional rituals of 10%, additional economic value of 6%, a hedgerow of 12% and a traditional medicine of 32%. The organ plant of Moringa oleifera which are leaves utilizing are 54% in Dayurejo and 60% in Jatiarjo Village. The number of Moringa oleifera was found 79 individuals in hamlet of Klataan and 35 in Tonggowah. Keywords: Ethnobotany, Prigen Pasuruan Moringa oleifera. ABSTRAK Kelor (Moringa oleifera) merupakan tanaman obat tradisional di Indonesia dan ia memiliki sumber nutrisi yang lengkap dan bermanfaat bagi kesehatan manusia baik akar, batang, daun dan buah. Pemanfaatan tumbuhan dalam kehidupan manusia adalah bagian dari Botani yang dapat di kaji melalui cabang ilmu Biologi yaitu Etnobotani. Tujuan penelitian ini untuk mengetahui manfaat, deskripsi dan distribusi tanaman Moringa oleifera di Desa Jatiarjo dan Desa Dayurejo Kecamatan Prigen Kabupaten Pasuruan. Penelitian ini menggunakan metode deskriptif yang meliputi: studi pustaka, pengamatan di lapangan, wawancara dilakukan secara terstruktur dan terbuka, analisis data, dan dokumentasi persebaran tanaman Moringa oleifera. Hasil dari penelitian ini menunjukkan adanya potensi tanaman Moringa oleifera di Desa Dayurejo sebagai obat tradisional 28 %, sebagai bahan pangan 30 %, sebagai tanaman pagar 20 %, ritual adat 10 %, dan tambahan nilai ekonomi 12 %, pada Desa Jatiarjo 40 % sebagai bahan pangan, 10 % ritual adat, 6 % sebagai tambahan nilai ekonomi, 12 % sebagai pagar dan 32 % sebagai obat tradisonal. Bagian organ tanaman Moringa oleifera yang di manfaatkan daun 54 % pada Desa Dayurejo dan 60 % Desa Jatiarjo. Jumlah Moringa oleifera yang ditemukan sebanyak 79 individu di Dusun Klataan dan 35 individu di Dusun Tonggowah. Kata kunci: Etnobotani, Prigen Pasuruan, Moringa oleifera.